Determining students’ mental models about the sun, earth and moon celestial objects for sustainable learning in astronomy education in Libya - Ahmed, Fathia (Net Journals, 2021)
The study aims to reveal students' mental models and perceptions regarding the concept of the celestial bodies, for instance, earth, sun, and moon. This research study was conducted as a case study focusing on qualitative data. This study also has used a sample formed of 5th-grade students, in the 2018–2019 academic year; the target sample is formed from 50 students at an elementary school in Libya. This study aimed to use the data collection tool, in addition, a test with three open-ended questions was used. Also, according to primitive, synthesis as well as scientific models, the data classification was used and analyzed. The result of this practical study has demonstrated that all the target samples have a synthesis of mental models that are not sufficiently compatible with scientific knowledge.
Keywords: 4. Education